Metode Bimbingan Tokoh Agama Dalam Memberikan Keterampilan Penyelenggaraan Jenazah Pada Masyarakat Kelurahan Pasir Panjang, Kota Jambi - Putri Wulandari (JIGC (Journal of Islamic Guidance and Counseling), 2022)
This research is motivated by the phenomenon that the community in the Pasir Panjang village RT.05 experiences a lack of education on the management of corpses. This can be seen from every community that dies, the families always call religious leaders for the management of the corpse because they do not understand the procedure for organizing the corpse. Therefore, this study aims to determine the method of guidance in providing skills in organizing corpses and the materials provided by religious leaders. This research is a field research where the data obtained through observation, interviews, and documentation. This study concludes that the method given by religious leaders has been successfully implemented in the community. And the community has been able to organize the bodies in RT.05 Pasir Panjang Village. It's just that currently giving a method of organizing corpses for children who are experiencing a few obstacles where religious leaders say that the obstacle in providing guidance is in the media for bathing or shrouding the corpse. Currently, the teacher only provides guidance, namely in terms of praying for the corpse.